Low peripheral levels of insulin growth factor-1 are associated with high incidence of delirium among elderly patients: A systematic review and meta-analysis. (July 2018) - Li, Dian-Jeng; Tseng, Ping-Tao; Stubbs, Brendon; Chen, Tien-Yu; Lin, Pao-Yen; Chen, Shiou-Lan; Thompson, Trevor; Adamis, Dimitrios; Chu, Che-Sheng
Highlights: The study provides a comprehensive and quantitative review of IGF-1 and delirium. IGF-1 might play a role in the pathogenesis in the delirium. Lower peripheral levels of IGF-1 could be associated with delirium in the elderly. Abstract: Introduction: Delirium, a serious condition observed in critically ill patients, clinically presents with impaired cognition and consciousness. The relationship between delirium and peripheral levels of insulin growth factor-1 (IGF-1) is unclear. Thus we conducted a meta-analysis to address this issue. Methods: Seven major electronic databases were searched from inception until October 2, 2017 to obtain relevant clinical variables to compare the difference in IGF-1 levels between delirious and non-delirious elderly in-patients. A random effects meta-analysis was conducted. Results: We studies 10 articles involving 294 delirious patients (mean age 73.0 years) and 604 non-delirious patients (mean age 76.9 years). We found that peripheral levels of IGF-1 in patients with delirium were significantly lower than in those without delirium (Hedges' g  = −0.209, 95% confidence interval [CI] = −0.393 to −0.026, p  = 0.025). Meta-regression analyses found that no variables such as percentage of cognitive impairment, mean age, and female proportion contribute to heterogeneity in terms of the entire population. Conclusions: Our data suggests that lower peripheral levels of IGF-1 could be associated with a higher incidence of delirium among elderly patients. Further prospective studies with larger sample sizes are needed to investigate the association between peripheral levels of IGF-1 and delirium.